Design of a nonlinear distributed parameter observer for a pressure swing adsorption plant - Bitzer, M.; Zeitz, M. (Journal of process control, 2002)
As an integral part of an advanced process monitoring and control scheme, the reconstruction of the spatial concentration, temperature, and pressure profiles of an oxygen production plant is studied by the design of a nonlinear observer with distributed parameters. The considered pressure swing adsorption process consists of two adsorbers and each adsorber of two layers. The design of the nonlinear observer with distributed parameters is illustrated for a single adsorption layer, which is described by six quasilinear partial differential equations and related boundary conditions. Thereby, a late lumping approach is used in order to design the injected correction functions in the observer equations and to introduce tuning parameters with a physical meaning. The observer is extended to the entire adsorption process and its simulation shows an excellent convergence behavior.